In vivo evaluation of efficacy and potency of Channa spp. extracts as anlgesic agent - Nur Indah Ahmad.
Discovery of newer drugs from natural resources provides alternative to the drugs already present. C. striatus had long reigned as the effective remedy for post operative pain, locally, where it is consumed as soup tonic. Studies had shown that the C. striatus extract had anti-inflammatory and analgesic properties. C. lucius, belongs to the same family as C. striatus, also believed to alleviate pain as C. striatus, despite no further study had been done to prove the claim. This study aim to compare the efficacy and potency of extracts from both Channa spp. Extracts as analgesic agent, in vivo and to determine their EC 10 and E max values. Five groups of mice were given C. striatus extracts and another five groups received C. lucius extracts at different doses, intraperitoneally. Thirty minute later, acute peritoneovisceral pain was induced in all mice using the writing test. The number of writing response was counted cumulatively for 30 minutes and percentage inhibition for each dose of extracts was counted and compared. GraphPad Prism Software was used to obtain the EC 50 and E max values. The higher the dose of extract given, the higher the percentage inhibition of writing response was obtained. C. striatus exerted a higher percentage inhibition of writhing response than that of C. lucius extract. The EC 50 value for C. striatus extract was 170 mg, lower than that of C. lucius, 174 mg. Therefore, C. striatus extract had a better potency than C. lucius extract. The E max value for C. striatus extract was 98.72% and C. lucius extract was 89.85%. Therefore, C. striatus exerted greated in vivo analgesic activity as compared to C. lucius. As a conclusion, C. striatus extract exerted greater in vivo analgesic activity as compared to C. lucius extract.